Sistem Administrasi Penerimaan Pajak Perhotelan di Badan Pendapatan Daerah Kabupaten Gorontalo - Annisa Adriana Maksud; Rustam Tohopi; Udin Hamim (Transbahasa, 2025)
This study was motivated by the low realization of hotel tax revenue in Gorontalo Regency, which has failed to meet the target for the past five years despite various policies being implemented. The objective of this study is to describe the hotel tax administration system at the Regional Revenue Agency of Gorontalo Regency, focusing on three main aspects: the tax collection system, the quality of services provided to taxpayers, and the utilization of information technology in tax administration. This research employed a descriptive qualitative approach using data collection techniques such as observation, in-depth interviews, and documentation. The findings reveal that the tax collection system applies a self-assessment method, in which taxpayers calculate, deposit, and report their taxes independently. However, the implementation of this method has not been accompanied by a satisfactory level of taxpayer compliance. In terms of services, tax officers have provided relatively good administrative services but have not been optimal in conducting socialization and education activities for taxpayers. Meanwhile, the utilization of information technology through the SIPADA application has been introduced to facilitate tax reporting and payment but has not yet operated effectively due to limited taxpayer understanding and several technical constraints. In conclusion, the hotel tax administration system in Gorontalo Regency has not yet functioned effectively. Therefore, strengthening supervision, improving service quality, and optimizing the use of information technology are essential to significantly and sustainably increase the region’s Own-Source Revenue (PAD).